2007
DOI: 10.1097/ajp.0b013e318074c986
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Prevalence of Pain in Fabry Disease and Its Response to Enzyme Replacement Therapy—A Retrospective Analysis From the Fabry Outcome Survey

Abstract: Pain is one of the most prevalent symptoms in Fabry disease with onset early in childhood. ERT with agalsidase alfa significantly reduces pain in this debilitating disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 36 publications
3
83
0
4
Order By: Relevance
“…Those treated with rh␣GAL also demonstrated significant reduction in pain scores. 115 Subsequent studies have indicated that ERT also stabilizes renal function if initiated in patients with urinary protein excretion Ͻ1 g/24 hours. ERT also slows progression of renal insufficiency in those with significant proteinuria, improves pulmonary and gastrointestinal symptoms, and reduces renal, cardiac, and CNS events.…”
Section: Therapymentioning
confidence: 99%
“…Those treated with rh␣GAL also demonstrated significant reduction in pain scores. 115 Subsequent studies have indicated that ERT also stabilizes renal function if initiated in patients with urinary protein excretion Ͻ1 g/24 hours. ERT also slows progression of renal insufficiency in those with significant proteinuria, improves pulmonary and gastrointestinal symptoms, and reduces renal, cardiac, and CNS events.…”
Section: Therapymentioning
confidence: 99%
“…Невропатическая боль, или акропарестезии, наи-более часто оказываются первым симптомом заболе-вания и встречаются у 60-80% детей с классической болезнью Фабри [16,17]. Акропарестезии -это дли-тельная, интенсивная, жгучая, колющая, изнуряющая боль, возникающая в дистальных отелах конечностей.…”
Section: этиология и патогенезunclassified
“…For example genetic factors can create a physiological problem without the phenotype e.g. the shortage of an enzyme in Gaucher's disease [57] and Fabry's disease [58]; however the nature or proteins which are involved in the immune function also influence cardiovascular health [25].…”
Section: The Relationship Between Sensory Input and Biological Inputmentioning
confidence: 99%